Supply chain management of thai parboiled rice for export - Wattanutchariya W. (2017)
© IEOM Society International. Although parboiled rice now forms about a quarter of Thai rice exports by quantity, its supply chain has yet to be documented. Therefore the objectives of this research are to study the supply chain of Thai parboiled rice for export, and to investigate the performance of supply chain management (SCM) based on Values Stream Mapping (VSM). Data were collected through interviews, focus groups, and questionnaires with key players in the supply chain including 249 farmers, 20 parboiled millers and 6 exporters. Through VSM, the current case scenario is analyzed alongside a proposed case scenario. Upon comparison, the number of activities can be reduced from 34 to 23 (reduction of 32.35%), the operation cost from 6,309 to 4,454 THB/Ton (reduction of 29.40%). The total process time from the rice field to the overseas market can be reduced from 5,373 to 4,755 hours, or 11.50%. Most activities occurred during the storage activities in the supply chain. Therefore, supply chain efficiency can be improved by reducing inventory period and increasing the direct connection network with the key players, which could lead to higher profits and faster responsiveness to importers. © IEOM Society International.